2020
DOI: 10.1080/0735648x.2020.1819375
|View full text |Cite
|
Sign up to set email alerts
|

Using estimates of undocumented immigrants to study the immigration-crime relationship

Abstract: The debate about undocumented immigration and its potential relation to crime continues to boil in the United States. We study this relationship by using two sets of estimates for the 2014 undocumented foreign-born population in U.S. metropolitan areas acquired from the Pew Research Center and the Migration Population Institute, 2013-2015 FBI Uniform Crime Report data, and 2011-2015 American Community Survey data from the U.S. Census Bureau, to model the association between undocumented immigration and violent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 71 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…Bui (2009) found first-generation immigrant youth were less likely to engage in delinquency and substance use than other youth. Light and Miller (2018) and Light et al (2020) both reported a negative relationship between undocumented immigration and violent crime in the U.S., while Adelman et al (2021) found a negative relationship between undocumented immigration and property crimes, and Adelman et al (2017) reported that foreign-born individuals are much less likely than native-born Americans to commit either violent or property crimes. Nowrasteh (2019) found that the arrest and conviction rates for both legal and illegal immigrants in Texas in 2017 were significantly lower than those of native-born Americans.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Bui (2009) found first-generation immigrant youth were less likely to engage in delinquency and substance use than other youth. Light and Miller (2018) and Light et al (2020) both reported a negative relationship between undocumented immigration and violent crime in the U.S., while Adelman et al (2021) found a negative relationship between undocumented immigration and property crimes, and Adelman et al (2017) reported that foreign-born individuals are much less likely than native-born Americans to commit either violent or property crimes. Nowrasteh (2019) found that the arrest and conviction rates for both legal and illegal immigrants in Texas in 2017 were significantly lower than those of native-born Americans.…”
Section: Literature Reviewmentioning
confidence: 96%
“…(2020) both reported a negative relationship between undocumented immigration and violent crime in the U.S., while Adelman et al. (2021) found a negative relationship between undocumented immigration and property crimes, and Adelman et al. (2017) reported that foreign‐born individuals are much less likely than native‐born Americans to commit either violent or property crimes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is a violation of the substantive tenets of the ecological school, a set of ideas that explained immigration and crime trends early in the 20th century and can explain them now. Yet, researchers continue referring to a Latino Paradox [35][36][37] or immigrant paradox [38][39][40][41][42].…”
Section: Long Live Social Disorganization Theorymentioning
confidence: 99%